2019
DOI: 10.1590/1677-5449.180111
|View full text |Cite
|
Sign up to set email alerts
|

Análise do grau de recanalização da trombose venosa profunda: estudo comparativo de pacientes tratados com varfarina versus rivaroxabana

Abstract: Resumo Contexto A trombose venosa profunda (TVP) afeta anualmente cerca de dez milhões de pessoas no mundo e tem como principais complicações a embolia pulmonar e a síndrome pós-trombótica. O tratamento padrão é a anticoagulação, que pode ser realizada com heparinas, antagonistas da vitamina K, fondaparinux ou, mais recentemente, com anticoagulantes orais diretos (direct oral anticoagulants, DOACs). Os anticoagulantes diminuem a progressão do trombo e facilitam os mecanismos trombolíticos naturais, fato conhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We mention a study that compared the recanalisation rate in patients treated with warfarin (Group I) and rivaroxaban (Group II) and showed that it was 10%, 52.5% and 78.9% at 30, 90 and 180 days in Group I and 55.3%, 83.5% and 92.4% in Group II respectively (P = 0.041). 18 Discussing the identified RF for VTE, we found that patients with moderate RF had an earlier favourable evolution (from the first month and over 50% at 3 months), probably related to their younger age, and patients with strong RF had the slowest rate of thrombus regression (only 43% at 1 year), probably connected with the later initiation of treatment in less symptomatic patients and with more frequent proximal localisation of DVT.…”
Section: Discussionmentioning
confidence: 81%
“…We mention a study that compared the recanalisation rate in patients treated with warfarin (Group I) and rivaroxaban (Group II) and showed that it was 10%, 52.5% and 78.9% at 30, 90 and 180 days in Group I and 55.3%, 83.5% and 92.4% in Group II respectively (P = 0.041). 18 Discussing the identified RF for VTE, we found that patients with moderate RF had an earlier favourable evolution (from the first month and over 50% at 3 months), probably related to their younger age, and patients with strong RF had the slowest rate of thrombus regression (only 43% at 1 year), probably connected with the later initiation of treatment in less symptomatic patients and with more frequent proximal localisation of DVT.…”
Section: Discussionmentioning
confidence: 81%
“…The female sex also appears to be a factor of better recanalization [ 22 ], as well as the absence of comorbidity [ 23 ]. The use of NOAC has been shown to be a better treatment than VKA for venous recanalization after deep LE-VT [ 24 ]. However, this study does not allow us to compare this result.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates not only the efficacy of LMWH in achieving recanalization but also highlights how recanalization is a continuous process that still occurs at 6 and 12 months. In a retrospective analysis, 33 a group of patients receiving UFH and VKA were compared with those on rivaroxaban. Recanalization at 30, 90, and 180 days for the UFH and VKA group was reported at 10%, 52.5%, and 78.9%, respectively.…”
Section: Duration Of Anticoagulationmentioning
confidence: 99%